Numerical Modeling of a Triangle Semi-Submersible Floating Wind Platform Under Wave–Current Flows - Shuai Li; Jungang Hao; Yajun Ren; Ling Zhu; Jing Yuan; Yiyong Dong (Journal of Marine Science and Engineering)
The semi-submersible platform is a widely used structure for supporting floating offshore wind turbines (FOWTs) in deep-sea environments where waves and currents interact. Understanding the impact of wave–current interaction (WCI) on hydrodynamic loading and the resulting platform response is essential for effective platform design. However, many existing ocean engineering software packages assume that wave and current loadings can be linearly superimposed. In this study, computational fluid dynamics (CFD) numerical simulations were performed to examine the dynamic response of a newly proposed triangle semi-submersible platform under various wave–current cases. The research underscores the significant influence of WCI on platform motion and loads, introducing nonlinearities that substantially affect both dynamic response and structural stability. Furthermore, the study reveals that WCI can mitigate vortex-induced motion (VIM), thereby enhancing platform stability by altering the force frequency, which no longer aligns with the platform’s natural frequency, thus preventing resonance. Additionally, the presence of current can intensify wave dynamics, leading to increased wave forces acting on the platform. These findings highlight the necessity of integrating WCI considerations into the design and optimization of floating wind turbine platforms to enhance their structural stability and operational performance.